JAK/STAT signaling in diabetic kidney disease - Liu, Yingjun; Wang, Wenkuan; Zhang, Jintao; Gao, Shuo; Xu, Tingting; Yin, Yonghui (Frontiers in Cell and Developmental Biology, 2023)
Diabetic kidney disease(DKD) is the most important microvascular complication of diabetes and the leading cause of end-stage renal disease worldwide. The Janus kinase/signal transducer and activator of transcription(JAK/STAT) signaling pathway, which is out of balance in the context of DKD, acts through a range of metabolism-related cytokines and hormones. JAK/STAT is the primary signaling node in the progression of DKD. The latest research on JAK/STAT signaling is helpful to determine the role of this pathway in the factors associated with DKD progression. The factors include renin-angiotensin system(RAS), fibrosis, immunity, inflammation, aging, autophagy, and EMT. This review epitomizes the progress in understanding the complicated explanation of the etiologies of DKD and the role of the JAK/STAT pathway in the progression of DKD as well as discusses whether it can be a potential target for treating DKD. It further summarizes the JAK/STAT inhibitors, natural products, and other drugs that are promising for treating DKD, and discusses how these inhibitors can alleviate DKD, so as to explore possible potential drugs, which will contribute to formulating effective treatment strategies for DKD in the near future.